Digital Image Watermarking in Wavelet Domain - Hitendra Suryavanshi; Amit Mishra; Shiv Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Internet allows individuals to share the information.  The shared information is like text, image, audio and video files.  This information sharing results in some problems such as copyright violation, unauthorized use of documents. Such problems can be solved by using a technique called as digital watermarking. This paper presents different aspects of watermarking and how it is useful for intellectual property protection on internet.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1745